A composite zonal index for biking attractiveness and safety. (March 2020) - Kamel, Mohamed Bayoumi; Sayed, Tarek; Bigazzi, Alexander
Highlights: Develop a comprehensive zone-based index to represent both biking attractiveness and cyclist crash risk. Develop Bike Attractiveness Index by employing Bike Kilometers Travelled and Bike Safety Index by employing cyclist crash data. The BAI consists of bike network density, centrality, weighted slope, land use mix, and recreational density. The BSI consists of bike network coverage, continuity, complexity, signal density, and recreational density. The correlation between the BAI and the BSI in Vancouver, Canada, is r = 0.11. Abstract: Zonal characteristics (e.g. built environment, network configuration, socio-demographics, and land use) have been shown to affect biking attractiveness and safety. However, previously developed bikeability indices do not account for cyclist-vehicle crash risk. This study aims to develop a comprehensive zone-based index to represent both biking attractiveness and cyclist crash risk. The developed Bike Composite Index (BCI) consists of two sub-indices representing bike attractiveness and bike safety, which are estimated using Bike Kilometers Travelled (BKT) and cyclist-vehicle crash data from 134 traffic analysis zones (TAZ) in the City of Vancouver, Canada. The Bike Attractiveness Index is calculated from five factors: bike network density, centrality, and weighted slope as well as land use mix and recreational density. The Bike Safety Index is calculated from bike network coverage, continuity, and complexity as well as signal density and recreational density. The correlation between the Bike Attractiveness Index and the Bike Safety Index in Vancouver is low (r = 0.11), supporting the need to account for both biking attractiveness and safety in the composite index.